Rabbinic Literature and the Christian Scriptures - Neusner, Jacob (The review of rabbinic Judaism, 2015)
The Rabbinic literature may be compared with the Christian Scriptures and vice versa, thus providing evidence of the beliefs held by authoritative sages of the two different communities of Judaism. The Rabbinic tradition is relevant to New Testament studies insofar as the two bodies of writings appeal to the same holy Scripture. By analyzing how they respond to that Scripture, we learn the choices people face and we better understand the context in which they made their decisions. Here, by evaluating one aggadic example and one halakhic one, we see how, in their treatment of Scripture, the Rabbinic literature and the New Testament appear to intersect but primarily part company. The result is a deeper comprehension of the distinctive ideologies and values of each tradition.